Nutritional Status of Adolescent and College Girl Students in Terms of Haemoglobin Levels and BMI - Padma, A. Sai; Devi, S. Manju; Rajani, D.; Vanitha, S. (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Healthy nutrition is the vital aspect of life and a proper diet with enriched nutritious contents provides better infant, child, and maternal health, stronger immune systems, safer pregnancy and childbirth, lower risk of non-communicable diseases, and longevity. Apart from knowing the significance of healthy nutrition by several studies and community programs, malnutrition has been an ever-existing problem in the world, especially in developing countries. Malnutrition includes both undernutrition and overnutrition where anemia and obesity are the two major nutritional disorders to list. The rapid economic development, urbanization, and globalization in many developing countries but with a lack of good nutrients and high-calorie intake of food are the major causative factors for these two disorders. This chapter discusses the types, prevalence, and causes of anemia along with factors leading to obesity in adolescent and college girls. A point of discussion on the association between anemia and obesity is added with possible suggestions to combat these nutritional disorders.